(untitled) (Academic Journal of Internal Affairs, 2020)
Radioactive materials have become an explicit target for criminal and terrorist organizations in recent years, as they can be effective tools for panic and serious economic damage generation when used in a variety of weapons (e.g. explosive devices capable of dispersing radioactive material). In addition, radioactive material has been used in several cases to commit crimes such as poisoning or radiation exposure to potential target persons. The most famous is the so-called ‘Litvinenko case’, in which a Russian intelligence officer was poisoned with polonium in 2006. In addition to the international cases, however, radioactive material is also found in Hungary time-to-time during home searches. Even the detection of these materials can be challenging in the absence of appropriate detection equipment. Their exact identification, collection and specific examination requires specialized expertise. If the crime scene personnel does not detect the presence of radioactivity at the scene in a timely manner (e.g, because it cannot be detected without measuring equipment), the persons working there may subsequently suffer serious damage to health, as well as large areas and objects can be contaminated by dispersed radioactive material. It can also cause serious economic damage. This article describes an operating procedure for the professional respond of crime scenes contaminated with radioactive material, developed by experts of the Hungarian National Police, National Bureau of Investigation, Criminal Forensics Department and radiologists at the Centre for Energy Research in the frame of a project supported by the Home Affairs Security Fund.